Tricholoma lishanense (Tricholomataceae, Agaricales), a new species from China revealed by morphology and phylogenetic analysis - Yang, Jia-Jia; Xu, Yu-Yan; Lv, Jing-Chong; Fan, Li (Phytotaxa, 2023)
Tricholoma lishanense is described and illustrated from northern China based on both morphological and molecular data. Phylogenetic analyses based on sequence data from the ITS locus resolved the new species in section Lasciva of Tricholoma. Tricholoma lishanense can be diagnosed by its overall white basidiomata with a fragrant and pleasant odor, very narrow lamellae, different phylogenetic position and habitat under oaks.